Adaptation of the narcissistic personality inventory among a portuguese sample of incarcerated juvenile offenders - Pechorro, Pedro Fernandes Santos (2016)
The aim of the present study was to assess the psychometric properties of the Narcissistic Personality Inventory (NPI) and two of its short forms (NPI-16 and NPI-13) among a Portuguese sample of male incarcerated juvenile offenders (N=221). Of these, only the NPI-13 short version demonstrated a good fit in terms of its factor structure. The NPI-13 also showed promising psychometric properties in terms of its internal consistency, convergent validity, discriminant validity, and criterion-related validity. Statistically significant associations were found with age of crime onset, crime seriousness, conduct disorder symptoms, alcohol abuse, and cannabis use. These findings justify the use of the NPI-13, especially its Entitlement/Exploitativeness dimension, among incarcerated male youths.